Śrīmadrūpagosvāmiviracita-Lalitamādhavanāṭakam : kayācit prācīnatippanyā samalaṅkrtam - Rūpagosvāmī, 16th cent (Krshṇadāsabābā, 1967)
About Krishna, Hindeu deity; includes a medieval anonymous commentary.